Measurement and Computational Modeling of Radio-Frequency Electromagnetic Power Density Around GSM Base Transceiver Station Antennas - P. Nassiri; M. Saviz; M. Helmi-kohnehShahri; M. Pourhosein; R. Divani (AUT Journal of Electrical Engineering, 2017)
Evaluating the power densities emitted by GSM1800 and GSM900 BTS antennas isconducted via two methods. Measurements are carried out in half a square meter grids around twoantennas. CST Microwave STUDIO software is employed to estimate the power densities in order fordetailed antenna and tower modeling and simulation of power density. Finally, measurements obtainedfrom computational and experimental methods were compared through the contour lines using thestatistical Surfer software. After measuring and simulating all values, it turns out that power density isgenerally lower than the permissible exposure limits although exceeds the limits in some sample points. According to the measurements, simulation error in stations GSM900 and GSM1800 are 10% and 8%,respectively. Findings from contour-line-maps illustrates that direct measurement method follows thesame emission pattern as the computational method does. It validates the computational approach andthe models attained for BTS power density estimation.